2021
DOI: 10.33899/rjs.2021.169975
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Optical Properties of ZnO Thin Film at Low Laser Intensity Using Z-Scan Technique

Abstract: In this work, a highly sensitive well-known z-scan technique was employed to study the nonlinear optical properties of Zinc Oxide thin films as a function of low laser fluencies. The transmissions of the continues-wave red laser diode with wavelength of (650 nm) were measured from the ZnO thin film sample with thickness of ( 425 nm). The thin film used in this study was deposited on the glass substrates based on atmospheric pressure chemical vapor deposition (APCVD) technique. The measurements were obtained at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Several reports [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ] employed the Z-scan technique to explore the NLO properties of ZnO thin films. The results revealed that ZnO thin films had reverse saturable absorption (RSA) and a negative nonlinear refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ] employed the Z-scan technique to explore the NLO properties of ZnO thin films. The results revealed that ZnO thin films had reverse saturable absorption (RSA) and a negative nonlinear refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable works have reported NLO parameters in ZnO thin films by RF magnetron spu ering, whose thicknesses were 500 and 1200 nm with reported values of = 4.74 × 10 cm/W and = 2.59 × 10 cm/W, respectively [33]. Also, a ZnO thin film sample with a thickness of 425 nm synthesized by atmospheric pressure chemical vapor deposition (APCVD) was used in z-scan measurements to observe the influence of different irradiances ranging from 166 to 218 W/cm 2 [34]. The results indicated a notable difference with variable irradiance, with values ranging from 9.2039 to 10.5511 cm/ The contrast in the n 2 sign can be explained considering a different physical energy transfer mechanism generated by multiphoton processes under thermal and electronic optical effects.…”
Section: Nonlinear Z-scan Measurements Resultsmentioning
confidence: 99%
“…The z-scan results indicate a positive nonlinear refractive index in the nanosecond regime. The sign in the nonlinear refractive index might vary depending on many factors responsible for the physical mechanisms of nonlinearity [42], material thickness, incident irradiance, and different preparation techniques, like RF magnetron sputtering [43] or chemical vapor deposition [44]. Also, previous works have reported that the crystallization form of the ZnO could have influenced its optical and NLO response.…”
Section: Results Of the Z-scan Analysismentioning
confidence: 99%